A solvent-based quick-drying organic silicon zinc aluminum coating and its preparation method and application
By using solvent-based fast-drying organic silicon zinc-aluminum coating, the synergistic effect of metal anti-rust powder and multi-component resins, rapid curing and high-performance coatings are achieved at room temperature, solving the problem of curing existing zinc-aluminum coatings under high temperature conditions, and meeting the protection needs of automobile brake discs.
Patent Information
- Application Number
- CN202411961347.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The existing zinc-aluminum coatings cure under high temperature conditions, have high energy consumption, and the coating is prone to powder and cracking in high temperature environments, and have poor protection performance, making it difficult to meet the needs of automobile brake discs.
Solvent-based quick-drying silicone zinc-aluminum coatings, including metal anti-rust powder, vinyl silicone resins, dispersants, organic solvents, curing accelerators and thickeners, are used to self-dry and quickly cure at room temperature to form a coating with good loss resistance and mechanical properties.
It achieves rapid curing at room temperature, low energy consumption, salt spray resistance of coating, high temperature resistance and good mechanical properties, meeting the protection needs of automobile brake discs.
Smart Images

Figure BDA0005217222240000021 
Figure BDA0005217222240000041 
Figure BDA0005217222240000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zinc-aluminum coatings, and in particular to a solvent-based quick-drying organic silicon zinc-aluminum coating and a preparation method and application thereof. Background Art
[0002] Brake discs are extremely important components in the automobile braking system and are directly related to the life safety of automobile users. Zinc-aluminum coatings have excellent high temperature resistance and salt spray resistance and are widely used in protective coatings for automobile brake discs.
[0003] However, most zinc-aluminum coatings currently need to be cured under high temperature conditions. For example, patent CN 1172135A points out that traditional chrome-free water-based zinc-aluminum coatings need to be cured at 320-360°C for 30 minutes. The coating disclosed in patent CN 1172135A requires a curing baking temperature of 355°C, which consumes very high energy, while the coating performance is not damaged, and the life span is only 300°C / 1h. In addition, the existing chrome-free water-based zinc-aluminum low-temperature self-drying coatings, such as the coatings disclosed in Chinese patent applications CN 106893485A and CN 111040556A, although the coating curing temperature is low, the cured coating will powder and crack after being used in a high temperature environment, and the protective performance will completely disappear, which is not suitable for the use conditions of automobile brake discs. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a solvent-based quick-drying organic silicon-zinc-aluminum coating and its application. The solvent-based quick-drying organic silicon-zinc-aluminum coating provided by the present invention has the advantages of self-drying at room temperature and fast curing speed, and the obtained coating is wear-resistant and has good mechanical properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a solvent-based quick-drying organic silicon-zinc-aluminum coating, comprising independently packaged solvent-based organic silicon-zinc-aluminum coating and a diluent;
[0007] The solvent-based organic silicon zinc aluminum coating comprises metal anti-rust powder, organic silicon resin, dispersant, organic solvent, curing accelerator and thickener; the metal anti-rust powder comprises flaky zinc powder, spherical zinc powder and spherical aluminum powder;
[0008] The organic silicone resin includes vinyl organic silicone resin, methyl silicone resin and epoxy siloxane;
[0009] The diluent includes one or more of an alcohol solvent, an ether solvent, an ester solvent and a hydrocarbon solvent.
[0010] Preferably, the solvent-based organic silicon-zinc-aluminum coating comprises, by weight:
[0011] 70-85 parts of metal anti-rust powder;
[0012]
[0013] The mass ratio of the flaky zinc powder, the spherical zinc powder and the spherical aluminum powder is (30-50): (30-50): (5-15).
[0014] Preferably, the particle size of the spherical zinc powder is 3 to 9 μm;
[0015] The particle size of the spherical aluminum powder is 3 to 7 μm;
[0016] The flake diameter of the flaky zinc powder is 3 to 9 μm.
[0017] Preferably, the mass ratio of the flaky zinc powder, the spherical zinc powder and the spherical aluminum powder is (30-50): (30-50): (5-15).
[0018] Preferably, the dispersant comprises a nonionic dispersant and / or an amphoteric dispersant.
[0019] The preferred curing accelerator includes one or more of titanate, aluminate, zirconate, cobalt naphthenate, calcium naphthenate, lead naphthenate, dibutyltin dilaurate and bismuth isooctanoate;
[0020] The thickener includes one or more of bentonite, fumed silica, modified urea solution and cellulose.
[0021] Preferably, the mass ratio of the solvent-based organic silicon-zinc-aluminum coating to the diluent is 100:2-5.
[0022] The present invention provides a method for preparing the above-mentioned solvent-based quick-drying organic silicon-zinc-aluminum coating, comprising the following steps:
[0023] Mixing the silicone resin and the thickener to obtain a first mixed material;
[0024] mixing an organic solvent and a curing accelerator to obtain a second mixed material;
[0025] The first mixed material is mixed with a dispersant and metal anti-rust powder to obtain a third mixed material;
[0026] The third mixed material is mixed with the second mixed material to obtain a solvent-based organic silicon-zinc-aluminum coating;
[0027] The solvent-based organosilicon-zinc-aluminum coating and the diluent are packaged separately.
[0028] The present invention provides the use of the solvent-based quick-drying organic silicon-zinc-aluminum coating as a protective coating.
[0029] Preferably, the application method comprises the following steps:
[0030] The solvent-based organic silicon zinc aluminum coating and the diluent are mixed to obtain the solvent-based quick-drying organic silicon zinc aluminum coating that can be used for construction;
[0031] Applying and curing the solvent-based quick-drying organic silicon-zinc-aluminum coating that can be used for construction on the workpiece to be coated to obtain an organic silicon-zinc-aluminum coating;
[0032] The curing temperature is 10-60° C. and the curing time is 5-40 minutes.
[0033] The invention provides a solvent-based quick-drying organic silicon zinc aluminum coating, comprising independently packaged solvent-based organic silicon zinc aluminum coating and a diluent; the solvent-based organic silicon zinc aluminum coating comprises metal anti-rust powder, organic silicon resin, a dispersant, an organic solvent, a curing accelerator and a thickener; the metal anti-rust powder comprises flaky zinc powder, spherical zinc powder and spherical aluminum powder; the organic silicon resin comprises vinyl organic silicon resin, methyl silicon resin and epoxy siloxane; the diluent comprises one or more of an alcohol solvent, an ether solvent, an ester solvent and a hydrocarbon solvent. In the present invention, the flaky zinc powder is suspendable, not easy to settle, and is friendly to the storage of coating components. At the same time, it is stacked and arranged like fish scales in the coating, which not only has a cathodic protection effect, but also has a certain shielding effect; the spherical zinc powder has a high specific gravity and good anti-corrosion function. With the help of a dispersant, it can be stacked on the flaky zinc powder arranged like fish scales to improve the density of the coating, thereby improving the salt spray resistance of the obtained coating under room temperature curing; the spherical aluminum powder will not float, and while improving the density of the coating, it has an inhibitory effect on the rust consumption of the flaky zinc powder and the spherical zinc powder, can reduce the loss of the coating, and extend the salt spray resistance time.
[0034] The present invention adopts vinyl silicone resin as resin raw material. Vinyl silicone resin contains unsaturated groups. Under the condition of curing accelerator, it can be quickly cured into film at room temperature, giving the coating room temperature quick drying and good film forming properties, but the carbon chain formed by cross-linking of vinyl unsaturated bonds cannot tolerate high temperature, and the carbon chain will be cracked at high temperature, the integrity of the coating is damaged, and the performance is reduced; at the same time, the organosilicon bonds linked to the vinyl will cross-link at high temperature to improve the cross-linking density and integrity of the coating. The two reactions increase and decrease, ensuring that the coating can be quickly cured into film at room temperature and at high temperature. Performance is not damaged; however, the molecular weight of vinyl silicone resin is small, which will make the coating cross-linking density high, and the coating is hard and brittle; the present invention uses methyl silicone resin and epoxy siloxane resin in combination, wherein the methyl silicone resin has a toughening effect, and the epoxy siloxane resin has the effect of improving the adhesion and mechanical properties of the paint film. The coating provided by the present invention has the advantages of self-drying at room temperature and fast curing speed, and the resulting coating has both good mechanical properties and excellent salt spray resistance and high temperature resistance. The invention utilizes the synergistic effect of multi-component resin and auxiliary agent to improve the construction performance, film-forming property, mechanical property and salt spray resistance of the solvent-based quick-drying organic silicon-zinc-aluminum coating.
[0035] The experimental results show that the coating formed by the solvent-based quick-drying organic silicon-zinc-aluminum coating provided by the present invention has the advantages of quick drying at room temperature, high solid content, and low energy consumption, and has excellent mechanical properties, excellent salt spray resistance and high temperature resistance, meeting the protection requirements of automobile brake discs. DETAILED DESCRIPTION
[0036] The present invention provides a solvent-based quick-drying organic silicon-zinc-aluminum coating, comprising independently packaged solvent-based organic silicon-zinc-aluminum coating and a diluent;
[0037] The solvent-based organic silicon zinc aluminum coating comprises metal anti-rust powder, organic silicon resin, dispersant, organic solvent, curing accelerator and thickener; the metal anti-rust powder comprises flaky zinc powder, spherical zinc powder and spherical aluminum powder;
[0038] The organic silicone resin includes vinyl organic silicone resin, methyl silicone resin and epoxy siloxane;
[0039] The diluent includes one or more of an alcohol solvent, an ether solvent, an ester solvent and a hydrocarbon solvent.
[0040] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0041] In the present invention, the solvent-based organic silicon-zinc-aluminum coating preferably comprises, by weight:
[0042]
[0043] In terms of parts by mass, the amount of the metal anti-rust powder is preferably 70 to 85 parts, more preferably 75 to 80 parts; as a specific embodiment of the present invention, the amount of the metal anti-rust powder is 70 parts, 75 parts, 80 parts or 85 parts. In the present invention, the metal anti-rust powder includes flaky zinc powder, spherical zinc powder and spherical aluminum powder. In the present invention, the flake diameter of the flaky zinc powder is preferably 3 to 9 μm, more preferably 5 to 7 μm. In the present invention, the flaky zinc powder is suspended, not easy to settle, and is friendly to the storage of the coating. At the same time, it is stacked and arranged like fish scales in the coating. In addition to the cathodic protection effect, it also has a certain shielding effect.
[0044] In the present invention, the particle size of the spherical zinc powder is preferably 3 to 9 μm, more preferably 5 to 7 μm. In the present invention, the spherical zinc powder has a high specific gravity and good anti-corrosion function. With the help of a dispersant, it is stacked on the flaky zinc powder arranged like fish scales, which can improve the density of the coating and the salt spray resistance of the obtained coating under room temperature curing.
[0045] In the present invention, the particle size of the spherical aluminum powder is preferably 3 to 7 μm, more preferably 4 to 6 μm. In the present invention, the spherical aluminum powder does not float, and while improving the density of the coating, it has an inhibitory effect on the rust and consumption of flaky zinc powder and spherical zinc powder, can reduce the loss of the coating, and extend the salt spray resistance time.
[0046] In the present invention, the mass ratio of the flaky zinc powder, spherical zinc powder and spherical aluminum powder is preferably (30-50): (30-50): (5-15), and more preferably (35-45): (35-45): (5-10).
[0047] Based on the mass fraction of the metal rust-proof powder, the amount of the vinyl silicone resin is preferably 10 to 15 parts, more preferably 10 to 14 parts; as a specific embodiment of the present invention, the amount of the vinyl silicone resin is 10 parts, 11 parts, 12 parts, 13 parts or 14 parts. In the present invention, the vinyl silicone resin is preferably vinyl trimethoxysilane and / or vinyl triisopropenoxy silane. In the present invention, the vinyl silicone resin contains unsaturated groups, and under the condition of a curing accelerator, it can be quickly cured to form a film at room temperature, and the carbon chain is cleaved at high temperature, which can give the coating quick drying at room temperature and good film-forming properties, salt spray resistance and other properties.
[0048] Based on the mass fraction of the metal rust-proof powder, the amount of the methyl silicone resin is preferably 3 to 5 parts; as a specific embodiment of the present invention, the amount of the methyl silicone resin is 3 parts, 4 parts or 5 parts. In the present invention, the methyl silicone resin is preferably one or more of phenyltrimethoxysilane, dimethyldimethoxysilane and methylphenyldimethoxysilane. In the present invention, the methyl silicone resin can improve the toughness of the coating.
[0049] Based on the mass fraction of the metal anti-rust powder, the amount of the epoxysiloxane is preferably 1 to 3 parts; as a specific embodiment of the present invention, the amount of the epoxysiloxane is 1 part, 2 parts or 3 parts. In the present invention, the epoxysiloxane is preferably KH 560 and / or MP 200. In the present invention, the epoxysilane has the effect of improving the adhesion and mechanical properties of the coating.
[0050] Based on the mass fraction of the metal rust-proof powder, the amount of the dispersant is preferably 0.2 to 1 part, more preferably 0.2 to 0.5 part; as a specific embodiment of the present invention, the amount of the dispersant is 0.2 part, 0.4 part, 0.5 part, 0.6 part, 0.8 part or 1 part. In the present invention, the dispersant preferably includes a nonionic dispersant and / or an amphoteric dispersant. In the present invention, the nonionic dispersant preferably includes a fatty alcohol polyoxyethylene ether; the amphoteric dispersant preferably includes a phosphate dispersant, and specifically preferably a polyether phosphate. In the present invention, the dispersant can disperse the metal powder evenly and has a directional arrangement effect on the metal powder during the coating film forming process.
[0051] Based on the mass fraction of the metal rust-proof powder, the amount of the organic solvent is preferably 2 to 5 parts, more preferably 3 to 4 parts. In the present invention, the organic solvent preferably includes one or more of ethylene glycol butyl ether, D40 solvent oil and xylene. In the present invention, the purpose of using the above-mentioned organic solvent is to adjust the volatilization speed of the coating in terms of construction performance, to prevent the coating film from being rough (volatilization too fast), sagging, and wrinkling (volatilization too slow) during dry spraying.
[0052] Based on the mass fraction of the metal rust-proof powder, the amount of the curing accelerator is preferably 0.5 to 1.0 parts; as a specific embodiment of the present invention, the amount of the curing accelerator is 0.5 parts, 0.6 parts, 0.8 parts or 1 parts. In the present invention, the curing accelerator preferably includes one or more of titanate, aluminate, zirconate, cobalt naphthenate, calcium naphthenate, lead naphthenate, dibutyltin dilaurate and bismuth isooctanoate. In the present invention, the role of the above curing accelerator is to promote the cross-linking and curing film formation of the vinyl silicone resin, while controlling the curing speed to avoid agglomeration and peeling during production and customer use.
[0053] Based on the mass fraction of the metal rust-proof powder, the amount of the thickener is preferably 0.5 to 1 part; as a specific embodiment of the present invention, the amount of the thickener is 0.5 part, 0.6 part, 0.8 part or 1 part. In the present invention, the thickener preferably includes one or more of bentonite, fumed silica, modified urea solution and cellulose. In the present invention, the modified urea solution is preferably BYK 410.
[0054] In the present invention, the diluent includes one or more of an alcohol solvent, an ether solvent, an ester solvent and a hydrocarbon solvent. In the present invention, the alcohol solvent is preferably propanol, the ether solvent is preferably propylene glycol methyl ether, the ester solvent is preferably propylene glycol methyl ether acetate, and the hydrocarbon solvent is preferably D40 solvent oil and / or trimethylbenzene. In the present invention, when the components of the diluent include multiple types of alcohol solvents, ether solvents, ester solvents and hydrocarbon solvents, the present invention has no special requirements for the ratio of various solvents.
[0055] In the present invention, the mass ratio of the solvent-based organic silicon-zinc-aluminum coating to the diluent is preferably 100:2-5, more preferably 100:3-5.
[0056] The present invention provides a method for preparing the above-mentioned solvent-based quick-drying organic silicon-zinc-aluminum coating, comprising the following steps:
[0057] Mixing the silicone resin and the thickener to obtain a first mixed material;
[0058] mixing an organic solvent and a curing accelerator to obtain a second mixed material;
[0059] The first mixed material is mixed with a dispersant and metal anti-rust powder to obtain a third mixed material;
[0060] The third mixed material is mixed with the second mixed material to obtain a solvent-based organic silicon-zinc-aluminum coating;
[0061] The solvent-based organosilicon-zinc-aluminum coating and the diluent are packaged separately.
[0062] In the present invention, the mixing of the silicone resin and the thickener is preferably carried out at room temperature, specifically, 18-25° C.; the mixing of the silicone resin and the thickener is preferably carried out by stirring; the stirring time is based on the uniform mixing of the silicone resin and the thickener.
[0063] In the present invention, the mixing temperature of the first mixture, dispersant and metal rust-proof powder is preferably ≤45°C, more preferably 15-45°C, and even more preferably 20-30°C; the mixing method of the first mixture, dispersant and metal rust-proof powder is preferably stirring; the stirring time is based on the uniform stirring of the zinc-aluminum powder.
[0064] In the present invention, the mixing temperature of the third mixture and the second mixture is preferably ≤45°C, more preferably 15-45°C, and even more preferably 20-30°C; the mixing method of the third mixture and the second mixture is preferably stirring; the stirring time is preferably 0.5-1h, more preferably 45min; and the stirring is carried out in a closed space.
[0065] The present invention adopts the above-mentioned mixing method, this is because:
[0066] ① The silicone resin and curing accelerator cannot be mixed together at once, otherwise they will solidify in the air environment, resulting in skinning in the coating liquid, and a solvent is needed to block the air. Therefore, the accelerator and solvent must be dissolved together.
[0067] ②The thickener needs to be dispersed in the silicone resin first. Otherwise, if metal powder has been added to the silicone resin, the viscosity of the components is high, and dispersing the thickener will easily lead to uneven dispersion. Therefore, the thickener needs to be evenly dispersed in the silicone resin first, and then the dispersant and metal powder are added and stirred to disperse evenly. Finally, the mixture of solvent and accelerator is added, and it is quickly stirred for a short time and packaged immediately.
[0068] ③ The present invention controls the temperature during mixing, on the one hand, to prevent the solvent from volatilizing in large quantities; on the other hand, to prevent the resin and the accelerator from reacting with the components in the air at high temperatures to accelerate the reaction, resulting in the formation of a skin in the coating liquid.
[0069] The present invention provides the use of the above solvent-based quick-drying organic silicon-zinc-aluminum coating as a protective coating. In the present invention, the protective coating is preferably a protective coating for automobile brake discs.
[0070] In the present invention, the application method comprises the following steps:
[0071] The solvent-based organic silicon zinc aluminum coating and the diluent are mixed to obtain the solvent-based quick-drying organic silicon zinc aluminum coating that can be used for construction;
[0072] The solvent-based quick-drying organic silicon-zinc-aluminum coating that can be used for construction is applied and cured on the workpiece to be painted to obtain the organic silicon-zinc-aluminum coating.
[0073] In the present invention, the solvent-based organic silicon-zinc-aluminum coating and the diluent are preferably mixed by stirring. The present invention has no special requirements for the stirring method, as long as the zinc-aluminum coating and the diluent can be mixed uniformly. In the present invention, the mixing is preferably carried out at room temperature, specifically, preferably 10 to 45°C, more preferably 20 to 30°C.
[0074] In the present invention, the material of the workpiece to be coated is preferably metal, more preferably cast iron or carbon steel. In the present invention, before the coating, the workpiece to be coated is preferably preheated, and in the present invention, the preheating temperature is preferably 40 to 60° C., more preferably 45 to 55° C. The present invention has no special limitation on the coating, and any coating known to those skilled in the art can be used.
[0075] In the present invention, the curing method is preferably standing at room temperature. In the present invention, the standing temperature is preferably 10 to 40°C, more preferably 10 to 35°C, and further preferably room temperature. In the present invention, the curing time is preferably 5 to 40 minutes, more preferably 5 to 30 minutes. The present invention can achieve a drying effect by standing at room temperature, so that the wet coating obtained by coating can be quickly dried and cured into a film.
[0076] The solvent-based quick-drying organic silicon-zinc-aluminum coating provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0077] The reagents used in the following examples are all commercially available.
[0078] Flake zinc powder: particle size is 3-9 μm, purchased from Eka, Germany;
[0079] Spherical zinc powder: particle size is 3-9 μm, purchased from Deyude Trading Co., Ltd.
[0080] Spherical aluminum powder: particle size is 3-7 μm, purchased from Xuyang Aluminum Pigment Co., Ltd.
[0081] Dispersant: fatty alcohol polyoxyethylene ether, model E1303, purchased from Haian Petrochemical; polyether phosphate, model AQ320, purchased from Desbaron;
[0082] Diluent: D40 solvent oil, xylene, ethylene glycol butyl ether, 150# solvent oil, purchased from Dow;
[0083] Modified urea solution: BYK 410, purchased from BYK, Germany;
[0084] Bentonite: Model Bentone 27, purchased from Hemmings Company;
[0085] Vinyl silicone resin: vinyl trimethoxysilane, model SICO-V171, purchased from Shandong SICO New Materials Co., Ltd.;
[0086] Methyl silicone resin: methylphenyl dimethoxysilane, model SICO-P112, purchased from Shandong Silicone New Materials Co., Ltd.;
[0087] Epoxysiloxane: KH 560, purchased from Nanjing Pinning Coupling Agent Co., Ltd.;
[0088] Accelerators: cobalt naphthenate and calcium naphthenate, purchased from Jinan Yunuo Chemical Co., Ltd.
[0089] Example 1
[0090] The solvent-based quick-drying organic silicon-zinc-aluminum coating was prepared according to the dosage of the substances in Table 1, and the method is as follows:
[0091] Mixing the silicone resin and the thickener to obtain a first mixed material;
[0092] mixing the solvent and the accelerator to obtain a second mixed material;
[0093] The obtained first mixed material, dispersant, flaky zinc powder, spherical aluminum powder and spherical zinc powder are mixed to obtain a third mixed material;
[0094] The third mixed material and the second mixed material were stirred and mixed for 45 minutes to obtain a solvent-based quick-drying organic silicon zinc-aluminum coating;
[0095] The obtained solvent-based quick-drying organic silicon zinc aluminum coating and the diluent are mixed in a mass ratio of 100:5 to obtain a solvent-based quick-drying organic silicon zinc aluminum coating suitable for construction use.
[0096] The above mixing was all carried out at 25°C.
[0097] Comparative Examples 1-2
[0098] The amounts of materials used in Comparative Examples 1 to 2 are shown in Table 1. The preparation method is consistent with that in Example 1, wherein the components with a content of 0 can be omitted to obtain a solvent-based quick-drying organic silicon-zinc-aluminum coating.
[0099] Table 1 Component dosage table of Example 1 and Comparative Examples 1-2 (parts by mass)
[0100]
[0101] Three batches of Example 1 and Comparative Examples 1-2 were prepared, and performance tests were performed respectively according to GMW 16284-2011, and the average values were taken. The performance test results obtained for Example 1 and Comparative Examples 1-2 are shown in Table 2.
[0102] Table 2 Performance test results of Example 1 and Comparative Examples 1-2
[0103]
[0104]
[0105]
[0106] As can be seen from Table 2, the solvent-based quick-drying organic silicon zinc aluminum coating provided by the present invention has the characteristics of quick drying at room temperature, high solid content, low energy consumption, excellent adhesion, excellent salt spray resistance and high temperature resistance, and meets the protection requirements of automobile brake discs.
[0107] Example 2
[0108] The solvent-based quick-drying organic silicon-zinc-aluminum coating was prepared according to the dosage of the substances in Table 3, and the method was as follows:
[0109] Mixing the silicone resin and the thickener to obtain a first mixed material;
[0110] mixing the solvent and the accelerator to obtain a second mixed material;
[0111] The obtained first mixed material, dispersant, flaky zinc powder, spherical aluminum powder and spherical zinc powder are mixed to obtain a third mixed material;
[0112] The third mixed material and the second mixed material are mixed to obtain a solvent-based quick-drying organic silicon zinc-aluminum coating;
[0113] The obtained solvent-based quick-drying organic silicon zinc aluminum coating and the diluent are mixed in a mass ratio of 100:5 to obtain a solvent-based quick-drying organic silicon zinc aluminum coating suitable for construction use.
[0114] The above mixing was all carried out at 25°C.
[0115] Comparative Examples 3-4
[0116] The amounts of materials used in Comparative Examples 3 to 4 are shown in Table 3. The preparation method is consistent with that in Example 2, wherein the components with a content of 0 can be omitted to obtain a solvent-based quick-drying organic silicon-zinc-aluminum coating.
[0117] Table 3 Component dosage table of Example 2 and Comparative Examples 3 to 4 (parts by mass)
[0118]
[0119] Three batches of Example 2 and Comparative Examples 3 to 4 were prepared, and the tests were performed according to GMW 16284-2011, and the average values were taken. The test results of Example 2 and Comparative Examples 3 to 4 are shown in Table 4.
[0120] Table 4 Test results of Example 2 and Comparative Examples 3-4
[0121]
[0122]
[0123]
[0124] As can be seen from Table 4, the solvent-based quick-drying organic silicon zinc aluminum coating provided by the present invention has the characteristics of quick drying at room temperature, high solid content, low energy consumption, excellent adhesion, excellent salt spray resistance and high temperature resistance, and meets the protection requirements of automobile brake discs.
[0125] Example 3
[0126] The solvent-based quick-drying organic silicon zinc aluminum coating was prepared according to the dosage of the substances in Table 5, and the method was as follows:
[0127] Mixing the silicone resin and the thickener to obtain a first mixed material;
[0128] mixing the solvent and the accelerator to obtain a second mixed material;
[0129] The obtained first mixed material, dispersant, flaky zinc powder, spherical aluminum powder and spherical zinc powder are mixed to obtain a third mixed material;
[0130] The third mixed material and the second mixed material are mixed to obtain a solvent-based quick-drying organic silicon zinc-aluminum coating;
[0131] The obtained solvent-based quick-drying organic silicon zinc aluminum coating and the diluent are mixed in a mass ratio of 100:5 to obtain a solvent-based quick-drying organic silicon zinc aluminum coating suitable for construction use.
[0132] The above mixing was all carried out at 25°C.
[0133] Comparative Examples 5-6
[0134] The amounts of materials used in Comparative Examples 5 to 6 are shown in Table 5. The preparation method is consistent with that in Example 3, and a solvent-based quick-drying organic silicon-zinc-aluminum coating is obtained.
[0135] Table 5 Component dosage table of Example 3 and Comparative Examples 5 to 6 (parts by mass)
[0136]
[0137] Three batches of Example 3 and Comparative Examples 5-6 were prepared, and the tests were performed according to GMW 16284-2011, and the average values were taken. The test results of Example 3 and Comparative Examples 5-6 are shown in Table 6.
[0138] Table 6 Test results of Example 3 and Comparative Examples 1-2
[0139]
[0140]
[0141]
[0142] As can be seen from Table 6, the solvent-based quick-drying organic silicon zinc aluminum coating provided by the present invention has the characteristics of quick drying at room temperature, high solid content, low energy consumption, excellent adhesion, excellent salt spray resistance and high temperature resistance, and meets the protection requirements of automobile brake discs.
[0143] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A solvent-based quick-drying organic silicon zinc aluminum coating, characterized in that: Includes independently packaged solvent-based silicone zinc aluminum paint and thinner; The solvent-based organic silicon zinc aluminum coating comprises metal anti-rust powder, organic silicon resin, dispersant, organic solvent, curing accelerator and thickener; the metal anti-rust powder comprises flaky zinc powder, spherical zinc powder and spherical aluminum powder; The organic silicone resin includes vinyl organic silicone resin, methyl silicone resin and epoxy siloxane; The diluent includes one or more of an alcohol solvent, an ether solvent, an ester solvent and a hydrocarbon solvent.
2. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1, characterized in that: The solvent-based organic silicon-zinc-aluminum coating comprises, by weight: The mass ratio of the flaky zinc powder, the spherical zinc powder and the spherical aluminum powder is (30-50): (30-50): (5-15).
3. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1, characterized in that: The particle size of the spherical zinc powder is 3 to 9 μm; The particle size of the spherical aluminum powder is 3 to 7 μm; The flake diameter of the flaky zinc powder is 3 to 9 μm.
4. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1 or 3, characterized in that: The mass ratio of the flaky zinc powder, the spherical zinc powder and the spherical aluminum powder is (30-50): (30-50): (5-15).
5. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1 or 2, characterized in that: The dispersant includes a nonionic dispersant and / or an amphoteric dispersant.
6. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1 or 2, characterized in that: The curing accelerator includes one or more of titanate, aluminate, zirconate, cobalt naphthenate, calcium naphthenate, lead naphthenate, dibutyltin dilaurate and bismuth isooctanoate; The thickener includes one or more of bentonite, fumed silica, modified urea solution and cellulose.
7. The solvent-based quick-drying organic silicon-zinc-aluminum coating according to claim 1, characterized in that: The mass ratio of the solvent-based organic silicon-zinc-aluminum coating to the diluent is 100:2-5.
8. The method for preparing the solvent-based quick-drying organic silicon-zinc-aluminum coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing the silicone resin and the thickener to obtain a first mixed material; mixing an organic solvent and a curing accelerator to obtain a second mixed material; The first mixed material is mixed with a dispersant and metal anti-rust powder to obtain a third mixed material; The third mixed material is mixed with the second mixed material to obtain a solvent-based organic silicon-zinc-aluminum coating; The solvent-based organosilicon-zinc-aluminum coating and the diluent are packaged separately.
9. Use of the solvent-based quick-drying organic silicon-zinc-aluminum coating according to any one of claims 1 to 7 or the solvent-based quick-drying organic silicon-zinc-aluminum coating prepared by the preparation method according to claim 8 as a protective coating.
10. The use according to claim 9, characterized in that: The method of application comprises the following steps: The solvent-based organic silicon zinc aluminum coating and the diluent are mixed to obtain the solvent-based quick-drying organic silicon zinc aluminum coating that can be used for construction; Applying and curing the solvent-based quick-drying organic silicon-zinc-aluminum coating that can be used for construction on the workpiece to be coated to obtain an organic silicon-zinc-aluminum coating; The curing temperature is 10-60° C. and the curing time is 5-40 minutes.
Citation Information
Patent Citations
Chromium-free zinc aluminum coating with low sintering temperature, as well as preparation method and application thereof
CN106893485A
Water-based fluorocarbon chromium-free zinc-aluminum coating and preparation method and application thereof
CN111040556A
Water-reducible coating composition for providing corrosion protection
CN1172135A